Miguel Ángel Morón, La Taxonomía de los Melolonthidae (Coleoptera: Scarabaeoidea) de México y la difusión de su conocimiento - Halffter, Gonzalo (Instituto de Ecología, A.C., 2018)
As a posthumous tribute to the work of Miguel Ángel Morón in the taxonomy of the Melolonthidae of Mexico, an analysis of his work is presented from two of his books and an entomological exhibition that gives rise to a third book.